Assessment of GPS-TEC with the IRI-2016 model, the IRI-Plas model and GIM-TEC during low solar activity at KMITL, Thailand - Udomchaibanjerd, Jumpon; Supnithi, Pornchai; Phakphisut, Watid; Hozumi, Kornyanat; Tsugawa, Takuya (My University, 2019)
We have assessed the ionospheric total electron content (TEC) variations which derived from dual frequency GPS receivers (GPS-TEC) at the KMITL, Thailand, called KMIT station. Then, we study TEC variations during the quiet geomagnetic condition in the low solar cycle, 2008 which is the lowest solar activity of the 24th solar cycle. The GPS-TEC is compared with the TEC prediction by the IRI-Plas model, the IRI-2016 model and the Global Ionospheric Maps (GIMs) by the International GNSS Service (IGS). The International Reference Ionosphere (IRI-2016), International Reference Ionosphere extend plasmasphere (IRI-Plas) and Global Ionosphere Maps (GIM-TEC) are model predicted total electron content (TEC). Also, the IRI-Plas has the plasmasphere extension up to 20,000 km, closed to observation TEC from the global positioning system. The GPS-TEC underestimates the IRI-Plas and GIM-TEC in all seasons whereas the IRI-2016 overestimates the GPS-TEC except the IRI-2016 is comparable to the GPS-TEC between 20.00-24.00 UT.
Keywords: GPS-TEC; IRI-2016; IRI-Plas